IMPLEMENTASI METODE HUNGARIAN UNTUK OPTIMASI BIAYA SERVIS BERBASIS WEB - Azhar; yunita (Jurnal Informatika dan Teknologi Komputer (J-ICOM), 2020)
The matrix is the composition of a mathematical system that can assist all forms of calculations and is directly related to numbers or exact values that are large or small. The effectiveness of solving matrix problems that occur in everyday life can affect the profit side of a company, the Hungarian method is one way to solve this problem. The implementation of the Hungarian method is related to the matrix which is usually used for the case of placing an object or subject in a company. The assignment case that occurred at Bengkel Buyung Tambon-baroh relates to cost optimization for workers with their respective abilities and skills. The problem of cost optimization is very necessary considering the work schedule and the income of the workers depending on the circumstances of the institution or company concerned. Matrix calculation application using web-based Hungarian method can produce values that are considered effective for solving the problem. Based on the test results, the application produces a final value in the form of optimal costs for workers at the Buyung Tambon Baroh Workshop with their respective abilities and skills.